(untitled) (Journal of the College of Education for Women, 2022)
Social risks posed a great challenge to the development path in Iraq, which resulted in widening the development gaps, whether these gaps were between rural and embargoed areas, or between Iraqi governorates, and the gender gap. Besides, the nature of the reciprocal relationship between the social risks and the development process requires the adoption of development trends that are sensitive to the risks that take upon themselves the prompt and correct response to these risks, away from randomness and confusion that Iraq suffered from for decades. However, currently, the situation has differed a great deal. This is because the size and types of such gaps have widened and become more complicated than before; a matter which has led to have clear development gaps due to the differences and distances ensued among the Iraqi governments, the areas of rural and urban, in addition to the gender gap. The research has adopted the social sampling method by building a scale consisting of (21) paragraphs and four-way answer alternatives (agree completely, agree, do not agree, do not agree at all). The scale has been applied to a sample of (100) sociology specialist respondents. The research reached several conclusions, the most important of which are: The nature of the rapid and continuous social changes imposed new forms of social risks that are not familiar before and which are difficult to deal with. The problem of persistent inequality at the level of societies and individuals is one of the most serious challenges that can generate new opportunities for more deadly social risks.